Measurements of the CKM angle γ at the LHCb experiment - Cheung, S (2016)
Two measurements of the Cabibbo-Kobayashi-Maskawa angle γ using B → DK and B0 → DK*0 decays are presented in this thesis. The subsequent D meson decays to the KS0π+π− and KS0K+K− final states are studied using a binned Dalitz plot analysis. The D strong-phase variation over the Dalitz plot is taken from measurements performed at the CLEO-c experiment, making the analysis independent of a model to describe the D decay amplitude. Both measurements are performed using proton-proton collision data collected by the Large Hadron Collider beauty (LHCb) experiment in 2011 and 2012, corresponding to an integrated luminosity of 3 fb−1 at centre-of-mass energies √s = 7 TeV and 8 TeV. The value γ= (62 +15−14)° is measured using B0 → DK*0 decays and γ = (71 ± 20)° is measured using B0 → DK*0 decays, with a second solution for each value corresponding to γ + 180°. The measurements are consistent with the world average value of γ.